A judicialização da saúde (medicamentos): uma ponderação entre o direito individual e o coletivo - Carvalho Júnior, Antônio Raimundo Barros de (2022)
The social right to health was elected by the Constitution as fundamental and carried out by the Unified Health System (SUS) universally to society. The agency is responsible for implementing public (collective) policies in its area and when it fails, there is a possibility for the citizen (individual) to obtain the medication not obtained administratively through the Judiciary. This student's interest in this topic arose from the professional practice translated into individual health demands, postulating the most varied treatments. Judicial decisions are the most diverse, usually benefiting the individual, and, despite problems and consequences of judicial intervention to be identified in the body of work, the program fulfills its function, albeit precariously. In this aspect, the problem was contextualized with historical, normative and sociological aspects. It is intended to demonstrate that the individual right cannot override the collective, and neither can the State despise the particular issues of its citizens. The work was carried out based on classes taught by teachers Maria Celeste Cordeiro Leite Santos, Willis Santiago Guerra Filho, Cláudio De Cicco and Ricardo Sayeg, in addition to bibliographic research, documentaries and consultations on the virtual pages of Brazilian and English public bodies, with a view to that the UK public health system was the foundation for the establishment of the national public health organization. It so happens that, as it requires a large financial contribution, the supply of drugs proves to be a problematic public policy (collective) when confronted with the right of the citizen (individual). From this conflict emerges the judicial intervention whose analysis constitutes the central object of this work